2018
DOI: 10.12669/pjms.343.14982
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of Prunella Vulgaris extracts against multi-drug resistant Escherichia Coli from patients of urinary tract infection

Abstract: Background and Objective:Escherichia Coli is the most common etiological agent of UTI and accounts for more then 100, 0000 hospitalization annually. The objective of this study was to investigate the antimicrobial activity of aqueous and ethanolic extracts of Prunella vulgaris against E. coli from urinary tract infection patients.Methods:Urine samples of forty four suspected patients from Tertiary Care Hospital Faisalabad were used in this study. Ethanolic and aqueous extracts of Prunella vulgris (PV), a medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 17 publications
1
14
0
3
Order By: Relevance
“…Multi-drug resistant bacteria are serious threat in clinical health settings and very challenging to treat infectious disease 8. From current study it was found that 84% of clinical isolates have multi-drug resistance pattern.…”
Section: Discussionmentioning
confidence: 71%
“…Multi-drug resistant bacteria are serious threat in clinical health settings and very challenging to treat infectious disease 8. From current study it was found that 84% of clinical isolates have multi-drug resistance pattern.…”
Section: Discussionmentioning
confidence: 71%
“…Aproximadamente 80% da administração de antimicrobianos são desnecessárias. O uso incorreto dos antimicrobianos desempenha um papel significativo no desenvolvimento de resistência entre os microrganismos, produzindo efeitos adversos significativos sobre a saúde humana (25).…”
Section: Resultsunclassified
“…A partir de um estudo realizado com Prunella vulgaris L., foi observado que essa espécie, quando utilizada com antibióticos convencionais, no tratamento de ITU, apresentou melhores resultados, aumentando a sua eficácia, reduzindo a toxicidade e proporcionando uma atividade antimicrobiana de largo espectro (25). 10.14450/2318-9312.v33.e1.a2021.pp18-30…”
Section: Resultsunclassified
“…Studies on the action of aqueous, alcoholic and hydroalcoholic extract have highlighted the antimicrobial, antifungal, and antiviral properties. The aqueous and hydroalcoholic extract of the species Prunella vulgaris L. revealed the anti-bacterial effect on Escherichia coli, Klebsiella pneumoniae, Proteus vulgaris, and on different Staphylococcus species (7)(8)(9). The methanolic extract of Prunella vulgaris L. (root) has demonstrated in vitro antiproliferative activity on different breast cancer cell lines: MCF-7, MDA-MB-231BO.…”
Section: Introductionmentioning
confidence: 99%